Analisis Yuridis Penggunaan Aplikasi Pengidentifikasi Nomor Telepon Terkait Resiko Pemrosesan Data Pribadi Tanpa Persetujuan: Juridical Analysis of the Use of Phone Number Identification Application Regarding Risks in Personal Data Processing without Consent - Napitupulu, Jeremy Patrick Christofel (Brawijaya Law Student Journal, 2023)
Jeremy Patrick Christofel Napitupulu, Moch. Zairul Alam, Diah Pawestri Maharani Fakultas Hukum Universitas Brawijaya Jl. MT Haryono No. 169 Malang e-mail: Patricknapit70@gmail.com Abstract The development of society and the use of the Internet in Indonesia have facilitated the exchange of information through information and communication technology. One such convenience is the phone number identification application, which collects personal data through a crowdsourcing system. This personal data is highly vulnerable to misuse for criminal or illegal profit, necessitating adequate legal protection. The phone number identification application is regulated under the Regulation of the Minister of Communication and Information Technology No. 5 of 2020 concerning the Operation of Electronic Systems within a Private Scope. However, given its operational methods and privacy policies, this application should also be examined under the Personal Data Protection Law because it involves personal data. Data processing principles in accordance with the regulation must be applied to ensure the protection of personal data. The importance of protecting personal data arises from the potential losses from breaches, which are often difficult to assess materially. Therefore, the assessment of the phone number identification application must consider both the regulation of the Ministry of Communication and Information Technology and the Personal Data Protection Law to optimally protect user privacy information. With proper legal protection, the risk of personal data misuse can be minmized, and public trust in information and communication technology can be enhanced. Keywords: Protection, Personal Data, Phone Number Identification Application Abstrak Perkembangan masyarakat dan penggunaan internet di Indonesia telah mempermudah pertukaran informasi melalui teknologi informasi dan komunikasi. Salah satu kemudahan ini adalah aplikasi identifikasi nomor telepon, yang mengumpulkan data pribadi dengan sistem crowdsourcing. Data pribadi ini sangat rentan disalahgunakan untuk kejahatan atau keuntungan ilegal, sehingga memerlukan perlindungan hukum yang memadai. Aplikasi identifikasi nomor telepon diatur dalam Peraturan Menteri Kominfo No. 5 tahun 2020 tentang Penyelenggaraan Sistem Elektronik Lingkup Privat. Namun, mengingat cara kerja dan kebijakan privasinya, aplikasi ini juga harus dikaji berdasarkan Undang-Undang Perlindungan Data Pribadi karena memuat data pribadi. Prinsip-prinsip pemrosesan data pribadi sesuai dengan peraturan perundang-undangan harus diterapkan untuk memastikan perlindungan data pribadi.Pentingnya perlindungan data pribadi disebabkan oleh potensi kerugian yang bisa timbul dari pelanggaran, yang sering kali sulit dinilai secara materi. Oleh karena itu, pengkajian aplikasi identifikasi nomor telepon harus memperhatikan peraturan Kominfo dan Undang-Undang Perlindungan Data Pribadi untuk melindungi informasi privasi pengguna secara optimal. Dengan perlindungan hukum yang tepat, risiko penyalahgunaan data pribadi bisa diminimalisir, dan kepercayaan masyarakat terhadap penggunaan teknologi informasi dan komunikasi dapat ditingkatkan. Kata Kunci: Perlindungan, Data Pribadi, Aplikasi Identifikasi Nomor Telepon